2014
DOI: 10.1093/schbul/sbu175
|View full text |Cite
|
Sign up to set email alerts
|

Schizotypy From a Developmental Perspective

Abstract: The schizotypy construct focuses attention on the liability to develop schizophrenia-spectrum disorders, yet traditionally, the schizotypy models have put more emphasis on stress-vulnerability interactions rather than developmental dynamics of emerging risk for psychopathology. Indeed, developmental accounts of this emerging personality trait have rarely been explicitly formulated. In this position article, we wish to convey some of the basic developmental tenets of schizotypy, and how they can inform high-ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 52 publications
(53 reference statements)
2
96
0
Order By: Relevance
“…As the literature is still unclear whether schizotypy and PEs index the same phenotype or measure different, but overlapping phenotypes (Debbane and Barrantes-Vidal, 2015;Torgersen, 1985); we conducted a sensitivity analysis that assumed both constructs index the same phenotype and calculated a composite severity score that captured the distribution of the sample on the total number of psychotic experiences and OBMT items…”
Section: Statistical Analysesmentioning
confidence: 99%
“…As the literature is still unclear whether schizotypy and PEs index the same phenotype or measure different, but overlapping phenotypes (Debbane and Barrantes-Vidal, 2015;Torgersen, 1985); we conducted a sensitivity analysis that assumed both constructs index the same phenotype and calculated a composite severity score that captured the distribution of the sample on the total number of psychotic experiences and OBMT items…”
Section: Statistical Analysesmentioning
confidence: 99%
“…PLEs by definition are transitory in nature and tend to disappear over time (symptom‐like approach). This phenomenon is characterized, in the majority of previous research, by positive experiences (eg, hallucinatory experiences, suspiciousness or magical ideation) (Debbané & Barrantes‐Vidal, ; Fonseca Pedrero & Debbané, ; Linscott & van Os, ). In particular, previous research has shown that schizotypal traits are a valid putative liability marker for psychotic spectrum disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests positive schizotypy overlaps substantially with positive symptoms of schizophrenia, but links to negative, disorganization and cognitive symptoms of schizophrenia may be weaker . Given this complexity, researchers are seeking links between dimensions of the schizotypy continuum and more endophenotypic constructs related to psychosis …”
Section: Electrophysiological Correlates Of Social Cognition In Subclmentioning
confidence: 99%
“…15 Given this complexity, researchers are seeking links between dimensions of the schizotypy continuum and more endophenotypic constructs related to psychosis. [16][17][18] Impairments in social cognition and behaviour are found in schizophrenia 19 and the schizophrenia prodrome, 20 stimulating the hypothesis that such impairments in schizotypy represent mechanisms of vulnerability. In schizophrenia, these impairments are associated with more basic neurocognitive performance, 21 as well as abnormalities in brain function as measured by eventrelated electrophysiological responses (ERPs) to social stimuli, e.g.…”
Section: Electrophysiological Correlates Of Social Cognition In Subclmentioning
confidence: 99%